INTELLIGENCE, TALENT AND GENIUS - de Araújo Filho, Walter Duarte; Silva, F.M (International Journal of Research -GRANTHAALAYAH, 2020)
In this paper discusses in an open manner the differences between intelligence, talent and genius. These three human capacities are often informally confused, but they have their own distinct characteristics. Talent is associated with the ability to execute intellectual and practical actions with an enormous degree of perfection. In this case, theory and practice become inseparable in the development of these actions. Genius permeates talent and intelligence, and has a differentiated ingredient, called imagination, which makes the holder of this intellectual capacity look further, crossing steps in the creation process.